Penerapan Pemberatan Pidana terhadap Tindak Pidana Penipuan dalam Rekrutmen Aparatur Sipil Negara: Studi Putusan Nomor 1175/Pid.B/2024/PN Mks - M Rayhan Ramadhan; Ambo Esa; Asrul Aswar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the application of sentence enhancement to perpetrators of fraud in the recruitment of civil servants (ASN) and examines the consistency of judicial reasoning in Decision No. 1175/Pid.B/2024/PN Mks. The research focuses on two main issues: the fulfillment of the requirements for sentence enhancement under Articles 52 and 486–488 of the Indonesian Criminal Code (KUHP), and the alignment of the judge’s considerations with the principles of criminal sentencing. Using a normative juridical method and employing statutory, case, and conceptual approaches, this research finds that the application of Article 378 KUHP was appropriate, as the elements of deception were proven. However, sentence enhancement under Articles 52 and 486–488 KUHP was not applied due to the absence of a functional connection between the perpetrator’s status as an ASN and the offense, as well as the failure to meet the formal requirements of recidivism. Although the decision is legally defensible in a formal sense, it lacks substantive completeness in addressing moral and sociological considerations. The perpetrator’s ASN status and prior conviction should reasonably serve as aggravating factors. The study concludes that while the decision is normatively consistent, it falls short of achieving substantive justice, particularly regarding public protection and the integrity of the civil service.